2011
DOI: 10.1590/s1516-18462011005000048
|View full text |Cite
|
Sign up to set email alerts
|

Coordenação motora fina de escolares com dislexia e transtorno do déficit de atenção e hiperatividade

Abstract: OBJETIVOS: descrever e comparar o desempenho da coordenação motora fina em escolares com dislexia e com transtorno do déficit de atenção e hiperatividade utilizando parâmetros de desempenho motor e idade cronológica da Escala de Desenvolvimento Motor. MÉTODO: participaram 22 escolaresdo ensino fundamental, de ambos os gêneros, na faixa etária de 6 a 11 anos de idade distribuídos em: GI: 11 escolares com transtorno do déficit de atenção e hiperatividade e GII: 11 com dislexia. Como procedimento, provas de motri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
2
6
0
5
Order By: Relevance
“…So, it is possible to state that the students with ADHD in this study presented visual-motor perception changes, thus corroborating studies described in international (2,14) and national (13,25) literature. Therefore, we can consider that difficulties to execute visual-motor perception and visual perception skills (reduced motricity) demonstrated in these students may compromise their handwriting performance, leading to dysgraphia, as described in the literature (21,26) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…So, it is possible to state that the students with ADHD in this study presented visual-motor perception changes, thus corroborating studies described in international (2,14) and national (13,25) literature. Therefore, we can consider that difficulties to execute visual-motor perception and visual perception skills (reduced motricity) demonstrated in these students may compromise their handwriting performance, leading to dysgraphia, as described in the literature (21,26) .…”
Section: Discussionsupporting
confidence: 90%
“…The student who does not develop this visual-motor integrative skill may present difficulties to write, that is, issues concerning the quality of writing, thus damaging school progress and favoring the appearance of emotional, behavioral, and learning problems (3) . In international (10,11) and national (12,13) literature, the relationship between dyslexia, learning disabilities, and changes in fine and gross motor coordination has been described, as well as the relationship between visual-motor perception and reading development of students with these learning disabilities. Throughout the years, the literature (14,15) has also described that one of the neurological conditions that compromises the VMI is the attention deficit hyperactivity disorder (ADHD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study 22 conducted on children with dyslexia and attention deficit and hyperactivity disorder demonstrated delayed in fine motor coordination in 100% of the sample, a fact that generated difficulties in tasks requiring dexterity such as spelling or tying one's shoes. Another study 14 observed signs of dysgraphia in pupils attending 6th grade of elementary school associated with various changes in learning.…”
Section: Discussionmentioning
confidence: 99%
“…ser comprometidos com alterações neurofuncionais nas regiões cerebrais responsáveis pela entrada, processamento e execução da informação, podendo afetar as crianças com TDAH. 16 Essas crianças têm pouca persistência de esforço para as tarefas e baixa atenção sustentada. No entanto, esse problema normalmente surge quando a mesma é atribuída a atividades aborrecidas, tediosas, prolongadas ou repetitivas que não têm apelo intrínseco a ela.…”
Section: Resultsunclassified